Response of Watermelon Cultivars against Viral Diseases under Natural Field Condition - and S.K. Pande, N.K. Sharma*, L.P. Awasthi, S. K. Singh (Journal of Phytology, 2011)
Watermelon (Citrullus lanatus (Thunb) Mastum and Nakai, synonyms: C. vulgaris) is a very common summer crop in World. It is also grown in lower Himalayan region to other parts of India such as Punjab, Haryana, Karnataka, Assam, West Bengal, Orissa ,Himanchal Pradesh, Tamil Nadu Rajasthan andÃ‚Â Uttar Pradesh. It is an excellent source of vitamin A and C and one cup of waterelon juice contain 48.59 mg of vit. C and 556.32 IU of vit. A besides 48 calorie of energy. At present almost all the cultivated varieties are found to be susceptible for virus infection. No symptomatic studies have been done on management of watermelon through host resistance. The present investigation was under taken to identify resistant/tolerant cultivar for viral diseases of watermelon.